Algae-specific colorful LEDs: Biotechnological drivers to biorefinery and photobiological platforms - Moreira, Bruno Rafael de Almeida [UNESP]; Frias, Yanca Araujo [UNESP]; Lima, Edivaldo Wilson de [UNESP]; Cruz, Victor Hugo [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Viana, Ronaldo da Silva [UNESP] (Elsevier, 2021)
Our systematic review sets out the state-of-the-art of algae-specific light-emitting diodes (LEDs). LEDs are semiconductor devices, and potentially the next generation of artificial illumination for energizing photoautotrophic algal systems. These addressable electroluminescence-injecting tiny bulbs render exceptional spectral and physicochemical properties for microalgae to grow and develop healthiest possible. Hence, they can enhance metabolic bioengineering of strains potentially capable of production of renewable bioenergy and integration into photobiological platforms. Thereby, the major sections of our meta-analytical overview go deepest possible into the development and implementation of specie-specific wavelengths to optimize (i) production of future-proof biofuels (e.g., biodiesel, bioethanol and biogas) and commercially valuable biomolecules (e.g., pigments, carbohydrates, proteins and fatty acids) to health-promoting dietary supplements and cosmeceuticals; (ii) biodepuration of environmental contaminants (e.g., heavy metals, minerals and drug-resistant antibiotics) of emerging concern worldwide and biofixation of CO2; (iii) power consumption; and (iv) economics of narrowband colorful LEDs, relative to wideband white LED and fluorescence-producing technologies, primarily compact lamps. Our paper is timely and provides valuable knowledge on tunable narrowbands with particularities to photoinduction and photomodulation of physiological and phytochromatic mechanisms in commercially relevant taxonomic groups. This will open up the horizons for making cutting-edge science in LEDs towards an essentially provocative yet emerging concept of fine-scale artificial photoautotrophic algal cultivation with more profitability and environmental-social responsibility.
Keywords: Addressable semiconductor devices; Light-emitting diodes; Light-harvesting pigments; photo(bio)synthetically active radiation; Photobioreactors; Photon flux density